Ruptured renal calyx mimicking leaking abdominal aortic aneurysm. (30th May 2012) - Allin, Benjamin; Chetwood, Andrew; Khoubehi, Bijan; DasGupta, Ranan
Abstract : The case of an 81-year-old man with a known 5.2 cm abdominal aortic aneurysm (AAA) and transitional cell carcinoma of the bladder who presented to the emergency department in painful clot retention is described. Approximately 5 h after starting bladder irrigation he developed a sudden onset of severe abdominal pain radiating to his back. Urgent CT scan (AAA protocol) revealed a rupture of the lower pole calyx of his right kidney and a stable aneurysm. Bladder irrigation was stopped and the patient settled with a catheter and simple analgesia. Given his significant co-morbidities, it was felt that surgical intervention for the underlying malignancy was inappropriate and the patient was discharged home. At last outpatient review, his renal function was at its baseline and he was suffering no ill-effects from the ruptured kidney.